2022
DOI: 10.1212/nxi.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Antineonatal Fc Receptor Antibody Treatment Ameliorates MOG-IgG–Associated Experimental Autoimmune Encephalomyelitis

Abstract: Background and ObjectivesMyelin oligodendrocyte glycoprotein antibody–associated disorder (MOGAD) is a rare, autoimmune demyelinating CNS disorder, distinct from multiple sclerosis and neuromyelitis optica spectrum disorder. Characterized by pathogenic immunoglobulin G (IgG) antibodies against MOG, a potential treatment strategy for MOGAD is to reduce circulating IgG levels, e.g., by interference with the IgG recycling pathway mediated by the neonatal Fc receptor (FcRn). Although the optic nerve is often detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, using the previously mentioned Seldeg approach, which consisted of an Abdeg Fc mutant fused with myelin oligodendrocyte glycoprotein (MOG), also reduced disease activity by exclusive degradation of pathogenic autoantibodies 157 , 158 . FcRn blockade also limited optomotor defects in a similar IgG-mediated EAE model of MS, reduced spinal demyelination and specifically altered macrophage infiltration into the spinal cord, with no differences in B cells, T cells or complement deposition 159 . In a passive transfer model of anti-muscle-specific kinase IgG4 from patients with MG, IgG1 MST-HN effectively ameliorated muscle weakness, weight loss and improved calf compound muscle action potentials, which correlated with lowering of serum pathogenic antibodies 160 .…”
Section: Pathophysiological Functions Of Fcrnmentioning
confidence: 85%
“…In addition, using the previously mentioned Seldeg approach, which consisted of an Abdeg Fc mutant fused with myelin oligodendrocyte glycoprotein (MOG), also reduced disease activity by exclusive degradation of pathogenic autoantibodies 157 , 158 . FcRn blockade also limited optomotor defects in a similar IgG-mediated EAE model of MS, reduced spinal demyelination and specifically altered macrophage infiltration into the spinal cord, with no differences in B cells, T cells or complement deposition 159 . In a passive transfer model of anti-muscle-specific kinase IgG4 from patients with MG, IgG1 MST-HN effectively ameliorated muscle weakness, weight loss and improved calf compound muscle action potentials, which correlated with lowering of serum pathogenic antibodies 160 .…”
Section: Pathophysiological Functions Of Fcrnmentioning
confidence: 85%
“…Several studies have indicated reduced visual acuity in the rodent EAE model [ 71 , 73 , 74 , 75 ]. Visual acuity changes and RGC dysfunction have also been reported in MS patients [ 17 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…211 In MOG-associated EAE, treatment with an FcRn-antibody ameliorated disease severity. 212 Data in experimental neuritis: We could not identify any specific studies evaluating FcRn inhibitors in autoimmune neuritis models.…”
Section: Dmts For Other Autoimmune Disordersmentioning
confidence: 99%